2013
DOI: 10.1103/physreva.88.032504
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of molecular chirality by vibrational Raman scattering

Abstract: In this study, we apply the monitoring master equation describing decoherence of internal states to an optically active molecule prepared in a coherent superposition of non-degenerate internal states in interaction with thermal photons at low temperatures. We use vibrational Raman scattering theory up to the first chiral-sensitive contribution, i.e., the mixed electric-magnetic interaction, to obtain scattering amplitudes in terms of molecular polarizability tensors. The resulting density matrix is used to obt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…We carefully analyzed all contained effects at weak-and strong-coupling limits. The resulting master equations in (11) and (33) were solved via a set of coupled differential equations in (28) and (37), characterizing optical activity of the en-semble. We showed that at high-temperature limit, the decoherence effects resulted from the chiral interactions can discriminate two chiral configurations, stabilized due to tunneling process (FIG.…”
Section: Resultsmentioning
confidence: 99%
“…We carefully analyzed all contained effects at weak-and strong-coupling limits. The resulting master equations in (11) and (33) were solved via a set of coupled differential equations in (28) and (37), characterizing optical activity of the en-semble. We showed that at high-temperature limit, the decoherence effects resulted from the chiral interactions can discriminate two chiral configurations, stabilized due to tunneling process (FIG.…”
Section: Resultsmentioning
confidence: 99%
“…For an isolated chiral molecule, the asymmetry is merely resulted from the internal chiral interactions i.e., the parity-violating weak interactions [3,39]. For a chiral molecule in interaction with the environment, however, the external chiral interactions e.g., the dispersion intermolecular interactions [5] and interaction with the circularlypolarized light [28] are the main source of asymmetry. An asymmetric double-well potential can be represented by a quartic potential including a linear term…”
Section: Modelmentioning
confidence: 99%
“…This stabilization problem of chiral molecules has been explained previously with the exceedingly long tunneling time [1] between |L and |R and/or introducing party-violating terms [2][3][4][5][6][7] in the molecular Hamiltonian, by considering the single molecule as an isolated system. Later on, it is found that the above mechanisms are not sufficient to explain the observed stabilization of some kinds of chiral molecules [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%